PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP PRICE EARNING RATIO - Siti Kustinah (Globalwriting Academica Consulting & Publishing, 2019)
Specifically, the goal of this study was to investigate the relationship between profitability, liquidity, leverage, and firm size and the price earning ratio of Indonesian manufacturing enterprises. Data analysis is carried out using E-views version 9.0 in this study, which makes use of quantitative approaches. The information was gathered through the use of secondary data, specifically financial statements from the Indonesian Stock Exchange from 2017 to 2019. A total of 30 manufacturing companies were consulted in order to examine the general feasibility of the proposed model and to test its outcomes. Profitability, liquidity, and leverage were found to have a substantial impact on the price earning ratio, according to the findings. A further point to mention is that the size of the company does not have a substantial impact on the price earning ratio in Indonesian manufacturing companies.